2018
DOI: 10.1002/adem.201700986
|View full text |Cite
|
Sign up to set email alerts
|

The Corrosion Behavior of Mg5Y in Nominally Distilled Water

Abstract: This paper studies the macro and micro corrosion of Mg5Y in nominally distilled water. The Y-containing corrosion product film formed on the alloy surface provides some protection for the Mg matrix to the galvanic corrosion caused by Y-containing second-phase particles. In some cases, there is no corrosion of the matrix surrounding most of the second phase particles. However, about 2% of the second-phase particles in the as-cast Mg5Y causes micro-galvanic corrosion, resulting in 'bump' or 'volcano' shaped corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…While the work of Atrens and co‐workers on Mg corrosion is well known, perhaps the most extensive Australian investigation on Mg–REE alloys to date is that performed at Monash University, in conjunction with CSIRO . This work spans corrosion, microstructure, and mechanical properties, and a full reckoning is beyond the scope of the current article, but several interesting findings can be discussed.…”
Section: Rare Earth Application To Magnesium Alloysmentioning
confidence: 98%
See 4 more Smart Citations
“…While the work of Atrens and co‐workers on Mg corrosion is well known, perhaps the most extensive Australian investigation on Mg–REE alloys to date is that performed at Monash University, in conjunction with CSIRO . This work spans corrosion, microstructure, and mechanical properties, and a full reckoning is beyond the scope of the current article, but several interesting findings can be discussed.…”
Section: Rare Earth Application To Magnesium Alloysmentioning
confidence: 98%
“…This was proposed to arise due to the ability of Y to improve the stability/density of the oxide/hydroxide layer, much as seen in the ignition tests discussed previously . If the stability of the hydroxide film is sufficiently increased (particularly in mild/Cl − ‐free media), this appears to overcome the galvanic coupling effects from the intermetallic phases . Namely, in a study of Mg–Y binary alloys in nominally distilled water, it was observed that so long as the hydroxide layer in the immediate vicinity of a Mg–Y intermetallic is stable, the galvanic effect of that particle is negated despite the intermetallic particle itself not chemically differing relative to active particles .…”
Section: Rare Earth Application To Magnesium Alloysmentioning
confidence: 98%
See 3 more Smart Citations